The Effect of Marketing and Commitment to Consumer Satisfaction at the ENT Clinic of Hospital Dustira Cimahi City - Rita Zahara (Dinasti Publisher, 2024)
The purpose of this research departs from the problems that occur at the ENT Clinic of Dustira Hospital, Cimahi City. The purpose of this research relates to Marketing and Commitment to Customer Satisfaction, because there are still employees who do not understand a professional service. The variables that will be measured in this study are Supriyanto & Ernawaty Marketing (2010: 21) are Internal Marketing, Interactive Marketing, External Marketing, Commitment Theory according to Newstorm in Wibowo (2017: 215) including Affective Commitment, Continuing Commitment, Normative Commitment while Satisfaction according to Irawan (2014: 2) Product quality, Price, Service Quality, Emotional Factors, Cost, and other factors. The research method used is a correlational quantitative approach to find Marketing Relationships and Commitment with Customer Satisfaction at the ENT Clinic of Dustira Hospital, Cimahi City, how to collect data using saturated sampling techniques of 11 respondents. The research instrument is in the form of a questionnaire containing statements to respondents using the Likert scale method using the theory from Sugiono (2014). Based on data calculations of respondents' responses to Work Discipline, the responses are in the good criterion (70%), the response to Professionalism is in the good criterion (68%), while the Employee Performance is also in the good criterion (67%). The results of the correlation analysis calculation, there is a large influence with a value of 0.5 between variable X and variable Y. Determination analysis shows that it is known that the coefficient of determination is found in the Adjusted R Square value of 0.742, this means that the ability of the independent variable to explain the dependent variable is 74.2%, the remaining 26.8% of the explanation is the variable that affects but is not tested, the correlation coefficient test results state that H0 is rejected and H1 is accepted. Based on the results of the analysis of the discussion in this thesis, it is necessary to take various actions to further enhance the role of satisfaction and to improve or increase the marketing and commitment of the ENT Clinic of Dustira Hospital, Cimahi City. Thus it can be concluded that there is an Effect of Marketing and Commitment on Customer Satisfaction at the ENT Clinic of Dustira Hospital, Cimahi City.